Análisis de la cadena de valor del kit de Horno Turbo de 110 volt. En la empresa INOX Industrial: Elaboracion del manual de procedimientos. - Alluca Vizuete, Edwin Marcelo (2014)
Metalworking companies must face changing demands in the current market, with more competitive products in terms of price, quality and level of service. In this situation, the productive systems of companies must be adapted in order to respond to the demands of customers faster and with the lowest possible cost. This work comes from the need to know why there are delays and disorder in the productive process of the turbo oven kit line, within the company INOX INDUSTRIAL by using the Value Stream Mapping (VSM) tool which is part of the Lean Manufacturing philosophy.